Prevalence rate of musculoskeletal discomforts based on severity level among office workers - Shariat, Ardalan; Mohd Tamrin, Shamsul Bahri; Arumugam, Manohar; Danaee, Mahmoud; Ramasamy, Rajesh (De Gruyter Open, 2016)
There are a variety of body aches that fall under the umbrella term of Musculoskeletal Discomforts (MSDs). These can be distinguished based on the level of pain suffered by the patient, ranging from mild and sporadic to serious, constant and fatal. It has been suggested that a link exists between MSDs and risk factors involving one’s occupational conditions and physicality. Examining the prevalence rate of musculoskeletal discomforts based on the severity among office workers was the main objective of this study. In order to achieve this objective, we had, in February 2015, selected from a population of 20 000 Malaysian office workers, 753 subjects within the age range of 20-50 years who have had a minimum of a year’s working experience. For this study, a form of structured questionnaire, known as the Cornell questionnaire, has been evaluated and put to use. Under the watch of the researchers, the subjects were instructed to complete the questionnaire in the morning before they begin their respective jobs. Based on their responses, the Cornell questionnaire has revealed that at least one case of severe pain in the neck, shoulder or lower back, respectively, is suffered by 69.7% of the subjects. In the case of neck-related aches, 15% low pain, whereas 51% involved mild pain and 33.9% were cases of severe pain. That being said, 19.3% low pain in the lower back, while 50.7% suffered from mild pain and 30% had severe pain in the same region. Percentages of 34.9% for high severity, 45.4% for mild severity and 19.7% for low severity were simultaneously reported in the shoulder section. In a nutshell, the study has revealed that, in comparison with body aches in the arms, knees, upper back, forearms, wrists, hands, hips and thighs, the subjects are more vulnerable to body aches in the neck, shoulders and lower back.